The penguin best Australian short stories (Penguin, 1991)
Set in cities, in suburbia and in the outback, this selection of short stories explores the subtleties, the humour and the sadness of human life. This book includes stories by E. Dyson, E. Jolley, M. Wilding, P. Carey and T. Winton.